2020
DOI: 10.1134/s0006297920090011
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor: Key to Selective Intracellular Delivery

Abstract: Epidermal growth factor receptor (EGFR) is an integral surface protein mediating cellular response to a number of growth factors. Its overexpression and increased activation due to mutations is one of the most common traits of many types of cancer. Development and clinical use of the agents, which block EGFR activation, became a prime example of the personalized targeted medicine. However, despite the obvious success in this area, cancer cure remains unattainable in most cases. Because of that, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 230 publications
(212 reference statements)
0
17
1
Order By: Relevance
“…Additionally, EGFR amplification was found to be correlated with increased expression of KIF4A and KIF18B , while EGFR mutation was related to the decreased expression of KIF18B in LUSC. Since EGFR initiates signal transduction through a network of downstream pathways that activate transcription of target genes [ 67 ], such as signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated kinase (ERK), and mTOR, it might indirectly regulate KIF4A and KIF18B transcription via these pathways. In addition, the multivariate analysis suggested that KIF18B was an independent predictor of OS in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EGFR amplification was found to be correlated with increased expression of KIF4A and KIF18B , while EGFR mutation was related to the decreased expression of KIF18B in LUSC. Since EGFR initiates signal transduction through a network of downstream pathways that activate transcription of target genes [ 67 ], such as signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated kinase (ERK), and mTOR, it might indirectly regulate KIF4A and KIF18B transcription via these pathways. In addition, the multivariate analysis suggested that KIF18B was an independent predictor of OS in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…EGF and TGFĪ± are the endogenous ligands for EGFR. As such, EGFR binds to its ligands [ 42 ]. EGFR dimerizes with another EGFR and autophosphorylates following ligand binding, which results in a sequence of intracellular signaling events.…”
Section: An Outlook On the Lipid-dependent Cancer Pathwaymentioning
confidence: 99%
“…The EGFR signaling network plays a primary role in the growth, maintenance, and homeostasis of epithelial tissues [ 82 , 83 ]. Many different types of cancer (e.g., lung, colorectal, pancreatic, breast, ovarian, cervical, bladder, neuroendocrine, glioma head, and neck) are associated with abnormalities in the EGFR axis, either by receptor overexpression, disfunction due to mutations, and/or increased autocrine and paracrine production of its growth factors [ 82 , 83 ]. Consequently, a huge number of anticancer drugs targeting EGFR are under clinical use or development, an approach that became a prime example of personalized targeted medicine [ 82 ].…”
Section: Growth Factors Receptors (Gfr)mentioning
confidence: 99%
“…Consequently, a huge number of anticancer drugs targeting EGFR are under clinical use or development, an approach that became a prime example of personalized targeted medicine [ 82 ]. Furthermore, EGFR can mediate the endocytosis of external agents into cancer cells, as well as translocate to the nucleus and the mitochondria, for which these receptors have been intensively studied as targets for the delivery of several chemotherapeutic, radionuclides, immunotoxins, and photosensitizers [ 83 ].…”
Section: Growth Factors Receptors (Gfr)mentioning
confidence: 99%